(3CSeGA GdeZJGdjf ef GdCTQGa aj GdLGgdjI hGdGSdGe hCSeGA ef bJd ef GdTYQGA hef ZdHJ cfjJg Ydi GSeg hcfi GdTYQGA hCdbGHges - (3eMeO Hf MHjH Hf CejI Hf YeQh GdgGTej, HGdhdGA, CHh LYaQ GdHZOGOj, ef ehGdj Hfj GdYHGSs ((3jhSa Hf eMeO s)
(3ChdgG (B:s
(3CSeGA GdeZJGdjf ef GdCTQGa LPjeI GdGHQT Hf eGdc Hf age Hf ZGfe Hf OhS Hf YOfGf s
(3BNQgG (B:s
(3GdegJOjf Hf eYGhjI Hf MQedg Hf QSe YOi Hf bQGAI Je GdcJGH HMeO Gddg s
(3GfXQ GdbSe GdChd ef GdJGQjN HQbe (B35s
(3HChdgG NW GdYdGeI eMeO Hf eMehO GdJQcRi GdTfbjWis
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs